2018
DOI: 10.1007/s10936-018-9616-1
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Orthographic Boost for Ambiguous Words During Their Processing?

Abstract: Is there an orthographic boost for ambiguous words during their processing?The present study explores the issue of why ambiguous words are recognized faster than unambiguous ones during word recognition. To this end we contrasted two different hypotheses: the semantic feedback hypothesis (Hino & Lupker, 1996), and the hypothesis proposed by Borowsky and Masson (1996). Although both hypotheses agree that ambiguous words benefit during recognition in that they engage more semantic activation, they disagree as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The pattern of activation from the probe that is most similar to that in memory from the target would be the chosen alternative. Some language processing research involving the 2AFC task has assumed that the task isolates the encoding of orthography (e.g., Grossi et al, 2009;Haro et al, 2019). Grossi et al (2009) refer to the word superiority effect and pseudoword (i.e., legal nonword, e.g., LAPE) superiority effect in word identification tasks, such as lexical decision or 2AFC, whereby word stimuli exhibit better performance than legal nonwords, which exhibit better performance than illegal nonwords (e.g., GLWK).…”
Section: Two-alternative Forced-choice and The Isolation Of Orthographymentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of activation from the probe that is most similar to that in memory from the target would be the chosen alternative. Some language processing research involving the 2AFC task has assumed that the task isolates the encoding of orthography (e.g., Grossi et al, 2009;Haro et al, 2019). Grossi et al (2009) refer to the word superiority effect and pseudoword (i.e., legal nonword, e.g., LAPE) superiority effect in word identification tasks, such as lexical decision or 2AFC, whereby word stimuli exhibit better performance than legal nonwords, which exhibit better performance than illegal nonwords (e.g., GLWK).…”
Section: Two-alternative Forced-choice and The Isolation Of Orthographymentioning
confidence: 99%
“…
In the two-alternative forced-choice (2AFC) task, the target stimulus is presented very briefly, and the participants must choose between two options as to which was the presented target. Some past research (Grossi et al, 2009;Haro et al, 2019) has assumed that the 2AFC word identification task isolates orthographic effects, despite orthographic, semantic, and phonological differences between the alternative options. If so, performance should not differ between word target/nonword foil pairs and British/American word pairs, the latter of which only differ orthographically.
…”
mentioning
confidence: 99%
“…There still lacks a definite theoretical formulation which can be used to predict the interaction among the multiple meanings of L2 ambiguous words. In the field of word recognition, some studies have found differences between processing unambiguous words and ambiguous words (Klepousniotou and Baum, 2007;Klepousniotou et al, 2012;Haro and Ferré, 2018;Haro et al, 2019). For example, it takes less time to recognize ambiguous words than unambiguous words (Borowsky and Masson, 1996;Hino and Lupker, 1996;Haro and Ferré, 2018;Haro et al, 2019).…”
Section: The Current Studymentioning
confidence: 99%
“…In the field of word recognition, some studies have found differences between processing unambiguous words and ambiguous words (Klepousniotou and Baum, 2007;Klepousniotou et al, 2012;Haro and Ferré, 2018;Haro et al, 2019). For example, it takes less time to recognize ambiguous words than unambiguous words (Borowsky and Masson, 1996;Hino and Lupker, 1996;Haro and Ferré, 2018;Haro et al, 2019). Moreover, some studies further found homonym disadvantage and polysemy advantage compared to processing unambiguous words (Rodd et al, 2002;Beretta et al, 2005).…”
Section: The Current Studymentioning
confidence: 99%
“…In order to decide which of the 410 Spanish ambiguous words were psychologically ambiguous (i.e., they had more than one meaning for the participants), two criteria had to be met: (a) at least one associate had to be generated for the subordinate meaning (note that cases with 0.5 associates in the subordinate meaning were included, because one of the judges, but not the other, considered that there was one associate related to that meaning), and (b) the NOM had to be equal to or higher than 1.40. This was the same NOM criterion to distinguish between ambiguous and unambiguous words as that employed in previous studies (e.g., Haro, Comesaña, & Ferré, 2019;Hino et al, 2006). A total of 108 words were rejected because they did not meet both criteria.…”
Section: Overview Of the Measuresmentioning
confidence: 99%